International business and decentralized finance - Harvey, Campbell R.; Rabetti, Daniel (Journal of International Business Studies, 2024)
Abstract Over the last decade, the green shoots of a new economic order have emerged as decentralized technologies challenge traditional financial systems. Decentralized finance (DeFi) holds the potential to transform international business (IB) by offering accessible financial services across borders, disrupting traditional intermediaries, and promoting financial inclusion. While traditional fintech has challenged banks, DeFi operates outside legacy systems, leveraging blockchain technology and smart contracting to introduce a new range of products and services that provide first-movers with an upper hand to both expand their business across the globe as well realize cost savings on existing business. Despite offering advantages like efficiency, transparency, and security, DeFi faces regulatory uncertainties and scalability, adoption, and stability concerns. Our study explores how DeFi can seamlessly integrate into the IB space while addressing these challenges. In addition to offering insights for investors, multinational firms, and regulators, we also lay the groundwork for future IB research in the fintech domain. As the DeFi innovation unfolds, understanding and harnessing its potential can empower stakeholders to engage responsibly and effectively in this transformative landscape.